Understanding the Barriers to Optimal Nutrition in Uninsured and Underserved Adults at the CommunityCare Free Medical Clinic in Toledo, Ohio - Marino, Elizabeth Bedell; Thuppal, Hayavadhan; Marino, Christopher; Welch, Philip John (Journal of Student-Run Clinics, 2018)
Background: Healthful eating habits are crucial for obesity prevention and are often lacking among the underserved and uninsured. The CommunityCare Free Medical Clinic (CCFMC) exists to serve the primary and preventive health care needs of uninsured and underserved residents of greater Toledo. The goal this study was to better understand the barriers to achieving optimal nutrition in the CCFMC patient population. Methods: A series of five focus groups of CCFMC patients was conducted in July and August 2015 to better understand the underlying factors resulting in poor nutrition in this population. Participants (n=50) were between ages 18 – 65 and racially diverse. Focus group discussions were recorded, transcribed, and analyzed using the long-table approach. Participants responded to 8 questions pertaining to food insecurity and ranked four factors by level of influence on their food purchasing decisions: cost, taste, nutritional value, and ease of preparation. Results: Several themes emerged, such as shame and embarrassment about not being able to afford nutritious food and the reliance on television personalities for nutritional guidance. Participants shared numerous insights on how to improve nutrition-related interventions at CCFMC. The ranking activity revealed that cost and ease of preparation influenced purchasing decisions more than taste or nutritional value. Conclusions: Based on the focus group findings, we suggest student-run free clinics provide a dedicated website for announcing nutrition programs and events, include clinicians in nutrition conversations with patients, and broadcast informational videos in the clinic lobby to promote nutrition awareness and discourse.